Four colorful new species of dragon millipedes, genus Desmoxytes Chamberlin, 1923, from northern Thailand (Diplopoda: Polydesmida: Paradoxosomatidae) - Srisonchai, Ruttapon; Enghoff, Henrik; Likhitrakarn, Natdanai; Panha, Somsak (Zootaxa, 2016)
Four new dragon millipede species of the genus Desmoxytes from northern Thailand are described and illustrated: D. des sp. n. from Chiang Mai Province, D. breviverpa sp. n. from Phrae Province, D. takensis sp. n. from Tak Province and D. pinnasquali sp. n. from Phitsanulok Province. The new species were compared with type specimens of closely related species and were all found to exhibit explicit morphological differences from these. They can be distinguished from other members of Desmoxytes by the shape of the gonopods, the sternal process between male coxae 4, the pattern of spines or tubercles on the metaterga, and the shape of the paraterga. The coloration of all new species is clearly aposematic: ranging from purple-pink to red. The new species are discussed in relation to their congeners, and a distribution map is provided.